Mechanisms of pediatric ischemic strokes in COVID-19: a systematic review - Layug, Elbert John V.; Apor, Almira Doreen Abigail O.; Kuhn, Rudolf V.; Tan, Marilyn A. (Frontiers in Stroke, 2023)
Background Coronavirus disease 2019 (COVID-19) has been shown to cause vasculopathic and hemostatic derangements predisposing to cerebrovascular and thrombotic disorders in adults. Data in children, however, are limited to case reports and series. Given the unique risk factors and potential pathomechanisms in children, it is imperative to characterize stroke in children with COVID-19. Understanding these mechanisms is essential in drafting an appropriate management protocol to improve outcomes in a population where stroke carries higher disability-adjusted life years. Methods A systematic literature search was done in MEDLINE, EMBASE, Web of Science and Google Scholar using the terms “pediatric ischemic stroke,” “cerebral sinovenous thrombosis,” “SARS-CoV-2,” and “COVID-19.” Patient demographics, clinical profile, stroke risk factors, neuroimaging findings, interventions and outcomes were recorded. Results The search produced 776 records. After preliminary review of titles, abstracts and selected full texts, 52 articles comprising of 74 patients were studied. The cohort has slight female predominance (51.5%), with mean age of 9.2 years (±2SD 5.6). Pediatric ischemic strokes were categorized as arterial ischemic strokes (82.40%), cerebral sinovenous thrombosis (12.20%) and combined arterial and venous strokes (5.41%). Mechanisms of ischemic stroke included thrombophilia (47.3%), vasculopathies (27%) and cardioembolism (6.8%). Twenty cases (27%) had comorbidities predisposing to stroke and only 18.9% met the criteria for multisystem inflammatory syndrome in children (MIS-C). Outcomes ranged from complete recoveries (13/58), residual deficits (35/58), and mortalities (10/58). Conclusion This study presents a comprehensive summary of the currently available published literature on pediatric ischemic strokes in the background of COVID-19. The clinical profiles and outcomes of patients reviewed support prior hypotheses that the virus can cause both a vasculopathy and induce a derangement in the coagulation system, predisposing to ischemic strokes. Study registration This paper's protocol has been registered in PROSPERO with ID number CRD42022315219.